First isolation of a trh positive V. alginolyticus from Atlantic bluefin tuna (Thunnus thynnus) farmed in Turkey - Avsever, ML (Journal of the Hellenic Veterinary Medical Society, 2022)
Popularity of sushi-sashimi (raw-almost raw fish service) is increasing around the globe, and Atlantic bluefin tuna is among the most frequently used fish in these dishes. In this study, trh (Thermostable direct hemolysin-related hemolysin gene) positive Vibrio alginolyticus was isolated from the internal organs of two tuna sent to the laboratory from a farm in Aegean region of Turkey in 2014. Isolation was done by conventional microbiological methods and Vitek 2 Compact fully automatic identification device was used for identification. Isolate confirmation and investigation of trh-tdh (Thermostable direct hemolysin) gene existence were carried out by a Polymerase Chain Reaction (PCR) method. Two V.alginolyticus isolates from two tuna were found to be trh positive and tdh negative. trh is one of the important genes associated with pathogenicity in the Vibrio genus, and raw consumption of tuna infected with trh positive V.alginolyticus can cause serious food poisoning. The aim of this study is to report first isolation of trh positive Vibrio alginolyticus from two bluefin tuna cultured in the Aegean sea, to draw attention to possible dangers in raw-almost raw fish consumption and supply information for further epidemiological studies. However, more samples are necesary for mentioning the prevalence of high virulence food pathogens in tuna. However, due to their economic value, multiple tuna samples are rarely sent to laboratories for diagnostic purposes.